The university and the city. Changing and challenging geographies in the Milan Urban Region. - Balducci, Alessandro; Fedeli, Valeria (Routledge, 2014)
This article seeks to reconstruct the logic and effect of the ongoing relocation processes of strategic urban functions, such as the university, within the specific spatial, social, economic, and institutional context of the Milan region. The paper argues that it is possible to interpret the new geographies of the city-university relationship as both the cause and effect of an emerging post-metropolitan condition. At the same time, it shows that this relationship, although challenged and stressed over time, has nevertheless remained significant and indeed has played an important role in the production and reproduction of forms of "cityness" and urbanity.
Keywords: Stadtplanung; Hochschule; Hochschulstandort; Campus; Städtebauliche Einordnung; Standort; Geschichte; Regionalentwicklung; Hochschulplanung; Urbanität; Universitätsstandort; Transformation